Education during conflict: The effect of territorial control by insurgents on schooling - Nicole Stoelinga (Max Planck Institute for Research on Collective Goods, 2024)
This study shows that civilians' behavior can be severely affected by territorial control by an insurgent group, and that these effects can persist after the government regains control and the occupation ends. I consider a framework of civilian behavior under insurgent rule, where civilians have the option to cooperate with, or resist, rules imposed by insurgents. I exploit the temporary occupation of territory in Nigeria by Boko Haram, an insurgent group with a strong anti-educational stance, as a quasi-experiment. Behavior is measured through school participation among children. Using individual-level panel data, I compare children exposed to the insurgency with children exposed to both the insurgency and occupation. The main results show (i) an immediate, negative effect on school participation, especially for those sharing a social identity with the insurgents, exposed to violent rule enforcement, and facing social pressure to conform, (ii) these negative effects persist in the long-run for the first and second group only. The effects cannot be explained by well-documented mechanisms linking conflict to lower school participation, demonstrating the need to account for occupation, and not solely violence, when considering the impact of insurgencies on civilians.
hdl:21.11116/0000-000E-1EB5-5
Keywords: I24; D74; O10; 330; conflict; insurgency; rebel governance; education; development